Pengaruh Faktor Internal Dan Eksternal Terhadap Pangsa Pasar Perbankan Syariah Di Indonesia Selama Pandemi Covid-19 - Setiawan Budi Darsono; Saiful Anwar (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The Covid-19 pandemic in Indonesia has had a negative impact not only on the world of health, but also on the economic and banking sectors, politics, education, religion and social culture. This research aims to look at several internal and external factors in sharia banking that influence the market share of sharia banking in Indonesia during the Covid-19 pandemic. The data collection technique uses secondary data sourced from monthly report publication data on the Financial Services Authority (OJK) and bank websites in the period January 2020 - December 2021. Analysis was carried out using the multiple linear regression method, and processed using Stata 14.2. Based on the results of data processing, it shows that internal factors consisting of Disbursed Financing and Number of Branches have a positive effect, while Non-Performing Financing has a negative effect on the Sharia Banking Market Share in Indonesia during the Covid-19 Pandemic. Meanwhile, external factors Gross Domestic Product have a positive effect, and Inflation has a negative effect on the Sharia Banking Market Share in Indonesia during the Covid-19 Pandemic.